Oeuvre vs. Abstract Space: Appropriation of Gezi Park in Istanbul - Senem Zeybekoglu Sadri (Journal of Contemporary Urban Affairs, 2017)
The Gezi Park incidents of summer 2013 in Istanbul have marked a turning point in the political life and democracy in Turkey. The peaceful environmentalist protestations in central Gezi Park have turned into a countrywide upheaval against the neo-liberal and conservative policies of the government, pouring millions of people into streets in different cities. It was a time that Turkey witnessed the formation of a new type of public sphere that encompasses a variety of counter publics, and its spatial incarnation –the Gezi Commune-, reclaimed, created, shaped and inhabited by the free will of people. This was the instant creation of oeuvre through the appropriation of the urban space, and a spatial manifestation of reclaiming the right to the city. This article is a reflection on the possibility of creation of oeuvre in contemporary society, and a new way of architectural thinking and practice that can pave the way for it.